Lunar cycle and reproductive activity of Redbelly yellowtail fusilier, Caesio cuning in Karimunjawa National Park, Indonesia - Fabian Panji Ayodya; Diah Permata Wijayanti; Agus Sabdono (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ayodya FP, Wijayanti DP, Sabdono A. 2021. Lunar cycle and reproductive activity of Redbelly yellowtail fusilier, Caesio cuning in Karimunjawa National Park, Indonesia. Biodiversitas 22: 3075-3082. Redbelly yellowtail fusilier (Caesio cuning) is known as fish that has been widely distributed among Southeast Asian countries. Fishers in Indonesia especially target the species, causing the scarcity and depletion of the catch in many fisheries areas each year. One of the priority aspects in improving fisheries management in conservation areas is information regarding reproductive activities. Many reports suggested that the lunar cycle affects the reproductive activity of fishes. However, none of the studies reported on the effect of lunar cycle on the reproductive activity of C. cuning. This study aimed to explain the lunar cycle effect on the reproductive activity of C. cuning through gonadosomatic index (GSI), viscerosomatix index (VSI), and the observation of oocyte conditions. There were 374 individual fishes collected from Nyamuk Island, Karimunjawa from September to November 2020. Samples were taken in each phase and between major phase of the moon (new, first quarter, full, last quarter) during two lunar cycles. The results point out mature gonad (stage IV and V) was present around the new moon. The peak of female GSI occurred around the last quarter moon with figures 6.12 and 5.51% respectively. The condition of the mature oocyte and ovulation were present around the last quarter and the new moon. The condition indicates imminent spawning.